2005
DOI: 10.1159/000084347
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Clomiphene Challenge Test as Predictors of Outcome of in vitro Fertilization and Intracytoplasmic Sperm Injection

Abstract: One hundred and sixty-two consecutive patients undergoing in vitro fertilization (IVF) or IVF/intracytoplasmic sperm injection (ICSI) were studied to determine the effect of obesity on the outcome of this treatment and to evaluate the prognostic value of the Clomiphene Challenge Test (CCT) in controlled ovarian hyperstimulation. In this prospective clinical study, we assessed the mean number of stimulation days, the mean gonadotropin level/day, cancellation rate, the mean thickness of the endometrium, the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 34 publications
4
65
1
4
Order By: Relevance
“…Some authors have reported outcomes per cycle (Wittemer et al, 2000;Nichols et al, 2003;Dechaud et al, 2006), while others have chosen to report outcomes per woman (Wang et al, 2000;Krizanovska et al, 2002;Fedorcsak et al, 2004;van Swieten et al, 2005;Dokras et al, 2006). Except for three (Wang et al, 2000;Krizanovska et al, 2002;Nichols et al, 2003), all studies reporting outcomes per woman have only included one cycle per woman.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported outcomes per cycle (Wittemer et al, 2000;Nichols et al, 2003;Dechaud et al, 2006), while others have chosen to report outcomes per woman (Wang et al, 2000;Krizanovska et al, 2002;Fedorcsak et al, 2004;van Swieten et al, 2005;Dokras et al, 2006). Except for three (Wang et al, 2000;Krizanovska et al, 2002;Nichols et al, 2003), all studies reporting outcomes per woman have only included one cycle per woman.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…Krizanovska et al (2002) and van Swieten et al (2005) reported all cases with positive b-hCG as clinical pregnancy, while Wittemer et al (2000) have used 'initiated pregnancies' without a clear definition of this term. Wang et al (2000) measured the probability of achieving at least one clinical pregnancy per woman whereas Nichols et al (2003) defined clinical pregnancy as the presence of a gestational sac at 6 -7 weeks gestation, identified via transvaginal scan.…”
Section: Pregnancy Ratementioning
confidence: 99%
“…In a prospective evaluation of the effect of obesity in IVF/ICSI in 162 patients, it was observed that obese women had a 45% lower fertilisation rate when compared with normal-weight controls (van Swieten et al 2005). A prospective cohort study of 50 overweight (BMI O26 kg/m 2 ) and 50 normal controls (BMI 18-25 kg/m 2 ) observed that fertilisation rate was significantly reduced in overweight women (46.2 vs 61.3%, P!0.05; Salha et al 2001).…”
Section: Obesity and The Oocytementioning
confidence: 99%
“…Obesity has been reported to affect ovarian stimulation in women undergoing treatment. Reported effects include prolonged ovarian stimulation, increased dose requirement of gonadotrophin, increased incidence of follicular asynchrony and increased cancellation rates (Mulders et al 2003, van Swieten et al 2005, Balen et al 2006, Bellver et al 2006, Maheshwari et al 2007, Esinler et al 2008. In a cohort study of women with PCOS undergoing ovulation induction with either clomiphene or gonadotrophins, it was observed that elevated BMI negatively affected ovulation rates.…”
Section: Obesity and Assisted Conceptionmentioning
confidence: 99%
“…While some studies on IVF reported less oocytes being collected from women with higher BMI [7,8,[15][16][17][18] Perhaps the response to exogenous gonadotropins administered during a stimulated cycle varies by patients' BMI and this can affect the oocyte yield. In our study the number of oocytes collected in an unstimulated IVM cycle was not affected by the patient`s BMI.…”
Section: Discussionmentioning
confidence: 99%